FACTORS INFLUENCING MATERNAL ACTIONS TOWARDS CIRCUMCISION IN GIRLS IN PASAR PARGARUTAN VILLAGE, ANGKOLA TIMUR DISTRICT, SOUTH TAPANULI REGENCY - sihombing, eni monaliska; Ibrahim, Ibrahim (Universitas Teuku Umar, 2025)
Health is a fundamental human right and a key factor in determining the quality of human resources (HR). One factor influencing women’s health status is the maintenance of reproductive organ health, particularly the genital organs. However, one practice still carried out in the name of maintaining genital health is female circumcision (sirkumsisi). Female circumcision, also referred to as female genital cutting or female genital mutilation (FGM), is a tradition that has long existed in certain communities.The objective of this study was to identify the factors influencing mothers' decisions to circumcise their daughters in Kelurahan Pasar Pargarutan, Kecamatan Angkola Timur, Kabupaten Tapanuli Selatan.This was a descriptive correlational study using a cross-sectional approach. The total population consisted of 58 individuals, and the sampling technique used was total population sampling, meaning all 58 participants (third-year female students) were included. The analysis was carried out using logistic regression testing.Findings is The variables found to significantly influence mothers’ decisions to circumcise their daughters were Knowledge (p = 0.024 < 0.05), Medical support (p = 0.037 < 0.05). The variables found to have no significant influence were Attitude (p = 0.298), Family support (p = 0.837), Community leader support (p = 0.851), Religion (p = 0.092).Conclusion: The study concludes that only knowledge and medical support significantly influence a mother’s decision to perform circumcision on her daughter. Therefore, it is recommended that health workers increase efforts in educating the community about female circumcision, including the risks and the fact that it is prohibited by the government, so that the public can better understand the harmful consequences of this practice.Keywords: Knowledge, Attitude, Family Support, Medical Support, Support from Community and Religious Figures